Long-term efficacy and tolerability of Clozapine combined with Ziprasidone or Risperidone - Kuwilsky, Anna; Krumm, Bertram; Englisch, Susanne Angelika; Dreßing, Harald; Zink, Mathias (Pharmacopsychiatry, 2010)
Introduction: Treatment resistance in schizophrenia often leads to add-on of atypical antipsychotics to clozapine. Methods: In a randomized trial, we recently obtained evidence for comparable efficacy and differential side effects of clozapine in combination with ziprasidone (CZ, N=12) versus risperidone (CR, N=12). Here, we present the open-label, long-term evaluations of these patients after 26 and 52 weeks. Results: Sustained improvements of psychopathology as assessed by PANSS (positive and negative syndrome scale), SANS (scale for the assessment of negative symptoms), and HAMD (Hamilton depression scale) were documented in both subsamples being treated according to protocol, while dropouts reduced the study sample after 26 (CZ: reduced by −4; CR: −2) and 52 weeks (CZ: −0; CR: −5). We observed a slight increase of akathisia in the CZ group whereas general clozapine-associated side effects improved. Discussion: The combinations of clozapine with ziprasidone or risperidone exhibit long-term efficacy, but the level of evidence is limited. Further head-to-head comparisons of atypical antipsychotics as add-on to clozapine are necessary.